Sure anot : a campaign combating fake news on WhatsApp - Lim, Kelley Ruili (Nanyang Technological University, 2020)
This paper presents Sure Anot, the first public communication campaign in Singapore designed to educate 50-64 year olds in Singapore on combating the spread of fake news on WhatsApp. This social messaging application is the most used among our target audience, and has specific platform features that allow fake news messages to be forwarded easily. This campaign is initiated by four students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. Through a simple three-step Be Safe, Be Sure routine, older adults are empowered to fight the spread of fake news on WhatsApp. Within the span of three months, the campaign was covered by Singapore media, and was acknowledged at the national level by Minister for Communications and Information, Mr S Iswaran, in the Committee of Supply Debate 2020. Older adults exposed to our campaign showed an overall increase in: (i) knowledge on methods to fight fake news, (ii) perceived self-efficacy in fighting fake news on WhatsApp, and (iii) intention to adopt the Be Safe, Be Sure routine, as compared to non-exposed older adults. At the point of submission, Sure Anot has successfully collaborated with private hire company Grab and Black Dot Research, independent fact-checking organisation, to develop ways in which the campaign can be sustained beyond its academic deadline. Future directions, limitations and future recommendations are discussed in the paper. Relevant documents and data sets can be found in the appendices of this paper.